INTERACTION BETWEEN LU CATIONS AND 2:1 ALUMINOSILICATES UNDER HYDROTHERMAL TREATMENT - Alba M.D.; Chain P. (My University, 2005)
Smectites are considered to be an important component in backfill barriers due to their marked swelling and high cation exchange capacity. Both properties are affected considerably when these clays transform under natural conditions. However, we have recently described a chemical interaction between high-activity radionuclide simulators and smectites which could prove to be effective at immobilizing radionuclides definitively. Investigating the efficiency of this mechanism, independent of bentonite ageing, is a challenge. For this purpose, the reactivity shown by a non-expandable layered aluminosilicate, muscovite, has been compared to that shown by an expandable one, beidellite. Both samples were treated hydrothermally with a solution of lutetium nitrate, and the transformations were studied by X-ray diffraction, nuclear magnetic resonance and scanning electron microscopy/energy dispersive X-ray analysis. Lutetium cations react with the silicon framework of both 2:1 layered aluminosilicates under hydrothermal conditions, and new phases, lutetium disilicate, kaolinite, boehmite and natrosilite are generated. The results demonstrate that the efficiency of the chemical mechanism is not determined by the swelling and the cation exchange capacity of 2:1 layered aluminosilicates. Thus, the rare earth disilicate formation might account for the success of the clay barrier, once bentonite has lost its swelling and cation exchange capacity. Copyright © 2005, The Clay Minerals Society.
Keywords: BENTONITE; CEC; HYDROTHERMAL ALTERATION; LUTETIUM CATIONS; NUCLEAR WASTE BARRIERS; RADIONUCLIDE BARRIERS